Kajian manajemen pengendalian waktu dan biaya pada proyek relokasi jalan masyarakat berdampak Bendungan Bulango Ulu Provinsi Gorontalo - Irjan, Irjan; Musa, Ratna; Watono, Watono (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study analyzes the relationship between time and cost control in the relocation project of community roads affected by the Bulango Ulu Dam in Gorontalo Province using the Line of Balance (LoB) method. This method is applied to design a more structured work schedule, identify activity stages, and minimize potential conflicts between tasks. The study results indicate that implementing the LoB method reduces the project duration to 33 weeks (7.7 months), compared to the existing schedule of 35 weeks. The two-week time savings significantly improve time efficiency. However, this acceleration results in an increase in total project costs, primarily due to higher labor and equipment usage. Calculations show that the LoB method requires higher costs than the existing schedule. This study confirms a reciprocal relationship between time and cost: time acceleration can affect cost increases, but cost efficiency can also be achieved through more targeted planning. The application of LoB provides a more measurable solution for managing construction projects, especially those involving repetitive tasks. The success of this method depends on strict supervision and schedule adjustments based on field conditions